2015
DOI: 10.1039/c5ta00656b
|View full text |Cite
|
Sign up to set email alerts
|

High photocurrent generation by photosystem I on artificial interfaces composed of π-system-modified graphene

Abstract: We report on the development of graphene-nanobiohybrid light-harvesting electrodes consisting of photosystem I and π-system modified graphene electrodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
64
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 68 publications
0
64
0
1
Order By: Relevance
“…The class of pyrene-derivative molecules has proven to be successful for stability, integration and preservation of the activity of redox active catalysts, such as the water-splitting Cu catalyst, 28 and photoactive enzymes, such as photosystem I, following their immobilisation on graphenebased electrodes. 29 Thus, the creation of a stable interface between graphene and a self-assembled monolayer (SAM) is of crucial importance to improve the DET in between the biological system and the metal electrode and to obtain a high performance device for biomolecular nanoelectronics.…”
Section: Introductionmentioning
confidence: 99%
“…The class of pyrene-derivative molecules has proven to be successful for stability, integration and preservation of the activity of redox active catalysts, such as the water-splitting Cu catalyst, 28 and photoactive enzymes, such as photosystem I, following their immobilisation on graphenebased electrodes. 29 Thus, the creation of a stable interface between graphene and a self-assembled monolayer (SAM) is of crucial importance to improve the DET in between the biological system and the metal electrode and to obtain a high performance device for biomolecular nanoelectronics.…”
Section: Introductionmentioning
confidence: 99%
“…Many groups have investigated the properties of PSI deposited onto various substrates. The most commonly used substrates are: chemically modified gold electrodes (Ciesielski et al 2010; Mukherjee and Khomami 2011), semiconductors like TiO 2 or ZnO (Mershin et al 2012; Yu et al 2015), and graphene (Gunther et al 2013; Feifel et al 2015). For most of the aforementioned works, the main evidence of intactness of the structure and function of PSI was its photoelectrochemical response.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Graphene owing to its high electrical conductivity, 15 high carrier mobility, 16 high power density, 17 large surface areas ($2600 m 2 g À1 ), 18 sustainability 19,20 and roll-to-roll compatibility, 21 offers an ideal choice for enhancing the electronic properties of optoelectronic materials when forming composites. 22,23 Azarang et al 24 have observed that ZnO/rGO composite (1.7 wt% rGO) shows enhanced photocurrent generation of 1.22 mA cm À2 , which is three times higher than that observed for pristine ZnO. Sookhakian et al 25 have found ZnS/rGO composite shows higher photocurrent generation of 1.9 mA cm À2 .…”
Section: Introductionmentioning
confidence: 99%